2017
DOI: 10.1038/srep42229
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of auxin transport genes identifies the hormone responsive patterns associated with leafy head formation in Chinese cabbage

Abstract: Auxin resistant 1/like aux1 (AUX/LAX), pin-formed (PIN) and ATP binding cassette subfamily B (ABCB/MDR/PGP) are three families of auxin transport genes. The development-related functions of the influx and efflux carriers have been well studied and characterized in model plants. However, there is scant information regarding the functions of auxin genes in Chinese cabbage and the responses of exogenous polar auxin transport inhibitors (PATIs). We conducted a whole-genome annotation and a bioinformatics analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…In this study, GARP transcription factor family gene BrKAN2 (Bra039528), a key regulator of leaf abaxial polarity, was identified by the association analysis of BSA-Seq analysis. It has been proven that the leafy head formation in Chinese cabbage can be affected by the uneven distribution of auxin in heading leaves [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, GARP transcription factor family gene BrKAN2 (Bra039528), a key regulator of leaf abaxial polarity, was identified by the association analysis of BSA-Seq analysis. It has been proven that the leafy head formation in Chinese cabbage can be affected by the uneven distribution of auxin in heading leaves [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism of leafy head formation in Chinese cabbage remains elusive. The leafy head development of Chinese cabbage is affected by diversity factors, such as phytohormones' uneven distribution [4], low temperature induction [5] and leafy shape [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chinese cabbage ( Brassica rapa L. ssp. pekinensis ), it is suggested that BrLAX genes may be involved in PAT during leafy head development (Gao et al, ). In rice, there are five members of the AUX1/LAX family (Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese cabbage with its leafy head is one of the most important vegetable crops in China. The leafy head ensures high yields, allows for nutrient storage and tolerance against both biotic and abiotic stresses (Tao et al, 2015;Gao et al, 2017). The Chinese cabbage leafy head is composed of a number of tightly packed heading leaves.…”
Section: Introductionmentioning
confidence: 99%